Identification of TRPM2 as a Marker Associated With Prognosis and Immune Infiltration in Kidney Renal Clear Cell Carcinoma - Sun, Lei; Zhang, Zijun; Zhao, Hang; Qiu, Miaoyun; Wen, Ying; Yao, Xiaoqiang; Tang, Wai Ho (Frontiers in Molecular Biosciences, 2022)
TRPM2 (transient receptor potential melastatin-2), a Ca2+ permeable, non-selective cation channel, is highly expressed in cancers and regulates tumor cell migration, invasion, and proliferation. However, no study has yet demonstrated the association of TRPM2 with the prognosis of cancer patients or tumor immune infiltration, and the possibility and clinical basis of TRPM2 as a prognostic marker in cancers are yet unknown. In the current study, we first explored the correlation between TRPM2 mRNA level and the prognosis of patients with different cancers across public databases. Subsequently, the TIMER platform and TISIDB website were used to assess the correlation between TRPM2 and tumor immune cell infiltration level. We found that 1) TRPM2 level was significantly elevated in most tumor tissues relative to normal tissues; 2) TRPM2 upregulation was significantly associated with adverse clinical characteristics and poor survival of kidney renal clear cell carcinoma (KIRC) patients; 3) TRPM2 level was positively related to immune cell infiltration. Moreover, TRPM2 was closely correlated to the gene markers of diverse immune cells; 4) High TRPM2 expression predicted a worse prognosis in KIRC based on different enriched immune cell cohorts; 5) TRPM2 was mainly implemented in the T cell activation process indicated by Gene Ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. In conclusion, TRPM2 can serve as a marker to predict the prognosis and immune infiltration in KIRC through regulation of T cell activation. The current data may provide additional information for further studies surrounding the function of TRPM2 in KIRC.